Proposition of Situational Based English Language Learning Theory (SBELLT): Influence from the Perspective of Systemic Functional Linguistics in the Western World to an Integration on Building a New Language Learning Theory in the Eastern World - Srinon, Udomkrit (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย; Vol 10 No 1 (2018): วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2020)
This article proposes Situational Based English Language Learning Theory (SBELLT) which is a principle and an assumption in that human being can learn a language well from situations and environmental factors. This theory is constructed and developed from the perspective of Systemic Functional Linguistics which proposes a principle in that language and learning occur in two contexts; context of culture and context of situation. Therefore, in this article the author proposes a new language learning theory based on situations to challenge linguists in that human being can learn a language well from situations they encounter and in social contexts which are around them. It is further discussed that based on this theory if appropriate situations are provided for language learning for learners, they can learn a language effectively through different situations and cultures which are embedded in various contexts, both in spoken and written modes. The author anticipates that this article will help fulfill a gap in the literature and offer better understanding on first, second and foreign language acquisition and development for linguists and educators involved and will lead to some applications of the theory in the future.